Dinâmica do enxofre no sistema solo e resposta das culturas à adubação sulfatada - Osorio Filho, Benjamin Dias (2006)
The conversion of pastures natives to grain production in soils with low clay and organic matter levels and/or the non-replacement of the exported sulfur by crops could cause a decrease on the availability of this nutrient to plants, whether the sulfur atmospheric depositions are low. There are few informations about the atmospheric contribution for soil fertilization in soils of Rio Grande do Sul, and the experiments with this nutrient are scarces. This work intends to quantify the sulfur deposition through rain and irrigation, the sulfur exported by plants and the sulfur available in soil and soil solution fluctuations, as well as the crops productivity. For these, two experiments were carried out at Soil Department of Federal University of Santa Maria. The first was installed at field in 2002, on Tipic Hapludult under no tillage system, in complete randomized blocks with four replications. The treatments were four sulfate levels (0, 15, 20 and 60 kg ha-1), which were applied before each culture, and two cultural rotations, in sub-plots. Sucking lisimeters were installed at 20 and 60 cm depth in each plot, for soils solution extraction. The deposition of atmospheric sulfur was quantified by a collector of precipitations. The culture productivity, the sulfur total amount in vegetal tissue, the sulfur exported and the amounts of available sulfate in soil and in water rain were evaluated. The second experiment, in greenhouse, were consisted of crops succession in pots (sorghum/bean/corn/soybean/corn/rye) with four soils kinds and four residual sulfate levels (0, 202, 403 e 807 g SO4 -2 pot-1), in completed randomized delineament, with four replications. After tree crops, soil samples were colleted from 0-10 cm and 10-20 cm soil layers to available sulfate analysis. The majority of results didn t show crops responses to sulfate fertilization, even with levels of available sulfate lower than the sufficiency level. The absence of response to sulfur founded in all crops tested by first experiment, might be associated with the sulfur atmospheric deposition by rain water, which determinative value was 3,2 kg ha-1 year-1. A corn culture, which was realized in greenhouse, was the only who showed increment in dry mass by sulfur addiction.